Automotive Clear Coat Polyurethane (Desmodur Z4470 + Different Desmophen) with Respect to Some Physical and Self-healing Properties - Shokuhi Rad, Ali; Binaeian, Ehsan; Mirabi, Ali (Asian Journal of Chemistry, 2011)
Desmodur Z4470 having isocyanate group was used to finding optimum formulation of polyurethane having self-healing property, with different desmophens as polyalcohol: Desmophen 670 BA, Desmophen 1800 and Desmophen A 665 both in the present and absent of ethylene glycol as the chain extender agent. The obtained results show that a hard polymer coating is obtained using Desmophen A665 polyalcohol in the absence of any chain extender. However a corrosion resistant and transparent coating is obtained using Desmophen 1800 and a ratio of NCO/OH = 2 for prepolymer formation stage and NCO/OH = 0.85 in polymerization stage by adding proper amount of ethylene glycol. This obtained polyurethane shows the best self-healing properties.